Oral administration of arabica green coffee extract increased fasting insulin, decreased fasting blood glucose, but did not decrease insulin resistance on wistar male rat (Rattus norvegicus) obese with diabetes mellitus - Maria Marissa Maharani; Anak Agung Gede Budhiarta; I Wayan Weta (Fakultas Kedokteran Universitas Udayana, 2021)
Background: Type 2 DM is characterized by defective insulin secretion and increased insulin resistance, with the main management is the control of behavior, such as diet. Green Coffee Arabica is one of the nutraceutical contains polyphenols which have anti-diabetic activity. This study aimed to prove that Arabica green coffee extract increases fasting insulin, decreases fasting blood glucose levels, and insulin resistance in male rat (Rattus Norvegicus) obese with diabetes. Methods: Experimental pretest-posttest groups study using 18 obese diabetic male albino rats. The control group was treated with placebo and the treatment group was treated with green coffee extract 300 mg/kgBW for 14 days. Fasting blood glucose and fasting insulin were measured before and after treatment. Results: There were a significant decrease of insulin levels in control group [from 6.59 to 3.67 mIU/L; p=0.011]. The change of insulin concentration between control group and treatment group were significant different statistically [-2.91 vs +1.57 mIU/L; p=0.024]. Significant decrease in fasting blood glucose in treatment group [from 162 to 120 mg/dL; p = 0.011]. The change fasting blood glucose between control group and treatment group were highly significant different statistically (+8 vs -44 mg/dL; p<0.001). Posttest HOMA-IR in treatment group and control group were not significant different statistically [2.49vs3.26; p=0.310] and the change HOMA-IR between control group and treatment group were not significant different statistically [-1.83 vs -0.497; p=0.145]. Conclusion: Oral administration of arabica green coffee extract increased insulin, decreased fasting blood glucose, but did not reduce insulin resistance on diabetic wistar rats.